2021
DOI: 10.1016/j.ijcard.2021.10.021
|View full text |Cite
|
Sign up to set email alerts
|

Screening for paroxysmal atrial fibrillation in primary care using Holter monitoring and intermittent, ambulatory single-lead electrocardiography

Abstract: Background: Timely detection of atrial fibrillation (AF) is important because of its increased risk of thromboembolic events. Single time point screening interventions fall short in detection of paroxysmal AF, which requires prolonged electrocardiographic monitoring, usually using a Holter. However, traditional 24-48 h Holter monitoring is less appropriate for screening purposes because of its low diagnostic yield. Intermittent, ambulatory screening using a single-lead electrocardiogram (1 L-ECG) device can of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 26 publications
2
4
0
Order By: Relevance
“…The intervention did not achieve higher AF yield than usual care over a 1-year period, mainly underscoring the efficacy of detecting AF in routine primary care in the Netherlands. 11,51 Our work subscribed to previous work which indicated that stroke location among patients with AF on post-stroke monitoring was most often non-lacunar hemispheric, with none or very few AF cases among patients with lacunar stroke/TIA. 6,41 We note here that stroke location in our data was primarily based on clinical symptoms as MRI was not routinely performed in all stroke/TIA patients.…”
Section: Comparison With Previous Worksupporting
confidence: 73%
See 1 more Smart Citation
“…The intervention did not achieve higher AF yield than usual care over a 1-year period, mainly underscoring the efficacy of detecting AF in routine primary care in the Netherlands. 11,51 Our work subscribed to previous work which indicated that stroke location among patients with AF on post-stroke monitoring was most often non-lacunar hemispheric, with none or very few AF cases among patients with lacunar stroke/TIA. 6,41 We note here that stroke location in our data was primarily based on clinical symptoms as MRI was not routinely performed in all stroke/TIA patients.…”
Section: Comparison With Previous Worksupporting
confidence: 73%
“…The intervention did not achieve higher AF yield than usual care over a 1-year period, mainly underscoring the efficacy of detecting AF in routine primary care in the Netherlands. 11 , 51 …”
Section: Discussionmentioning
confidence: 99%
“…Karregat et al invited 205 primary care patients aged ≥65 years with a negative 12-lead ECG to wear a Holter monitor for 2 weeks and to use a MyDiagnostick single-lead ECG device three times a day for 60 s ECG recordings. The sensitivity and specificity results of AF detection were 66.7 and 68.8%, respectively, ( 37 ). Svennberg et al used the Zenicor device in an AF screening study on 3,209 persons.…”
Section: Discussionmentioning
confidence: 99%
“…To overcome the limitations of ECG and Holter monitoring, event monitors, implantable loop recorders, and other wearable applications appeared and spread in last decade 13,14 . In particular, the artificial intelligence (AI)‐based single‐lead Holter test exhibits outstanding comfortability and accessibility 15 . Only one patch that adhered to the V2 location on the chest was easy to accept.…”
Section: Introductionmentioning
confidence: 99%
“… 13 , 14 In particular, the artificial intelligence (AI)‐based single‐lead Holter test exhibits outstanding comfortability and accessibility. 15 Only one patch that adhered to the V2 location on the chest was easy to accept.…”
Section: Introductionmentioning
confidence: 99%